The impact of socioenvironmental characteristics on domains of oral health-related quality of life in Brazilian schoolchildren - de Paula Janice Simpson; Leite Isabel Cristina Gonçalves; de Almeida Anderson Barbosa; Ambrosano Glaucia Maria Bovi; Mialhe Fábio Luiz (BMC, 2013)
Abstract Background Recent researches have pointed out the need to consider the functional and psychosocial dimensions of oral health, such as Oral Health-related Quality of Life (OHRQoL). The aim of this study was to investigate the influence of oral health status, socioeconomic factors and home environment of children on the four health domains of Child Perceptions Questionnaire (CPQ11-14). Methods A cross-sectional study was conducted in Brazil with a sample of 286 schoolchildren aged 12 years and their parents. The schoolchildren were clinically examined, and participants were asked to complete the CPQ11-14, as well as a questionnaire about home environment. In addition, a questionnaire was sent to each child's parents asking them about family socioeconomic status. The chi-square test and Poisson's regression analysis were performed. Results After adjusting for potential confounders, variables sex, monthly family income, mothers' education showed a statistically significant association with all health domains of the CPQ11-14. The family structure and presence of bleeding impacted on emotional (p = 0.0135), and social (p = 0.0010) well-being health domain scores. Orthodontic treatment need showed a strong negative effect on functional limitations domain score (p = 0.0021). Conclusions Clinical and socio-environmental factors had different impacts on domains of oral health-related quality of life, demonstrating the need to consider these conditions in planning strategies for the oral health of schoolchildren.